Precarious economies: capitalism's creative destruction in the age of neoliberal campus planning. Issue 2 (2nd April 2020) - Goodwin, Phillip; Casas, Rubén; Cintrón, Ralph; Hanan, Joshua Stanley; Rossman, Leslie L.; Sciullo, Nick J.
ABSTRACT: The Precarious Economies working group engaged the University of Nevada Reno's (UNR) Campus Master Plan (CMP) from the perspective of precarity—broadly understood as material conditions of vulnerability that threaten living bodies and are outside of one's control. Employing traditional and in situ methods of rhetorical analysis and fieldwork, we investigated how the creative destruction of Reno's emerging technology economy implicates people within precarity frames through facets of daily living including labor, housing, and transportation. Our mixed approaches allowed us to search for the material impacts of capitalism's development on the lives of Reno's residents and see the CMP's (re)distribution of precarity as a symptom of capitalism's creative destruction. In this essay, we describe the methods of our research and reflect on what the hybrid research approach of the working group teaches us about UNR/Reno and the contemporary function of capitalism.